Methods for conducting military operational analysis - Loerch, Andrew G.; Rainey, Larry B. (Military Operations Research Society, 2007)
Methods for Conducting Military Operational Analysis is a reference for practitioners in the field of military operational analysis. One of the many unique qualities about this text is that it focuses on analytical problems faced at the Office of the Secretary of Defense (OSD) or Service department levels. The editors have attempted to provide a balanced view of analytical methods employed by the various services. Many numerical examples are provided to further illustrate the described methods and techniques.